1998
DOI: 10.1002/(sici)1097-4628(19980307)67:10<1761::aid-app9>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Study of pyridinium-type functional polymers. II. Antibacterial activity of soluble pyridinium-type polymers

Abstract: ABSTRACT:The antibacterial activity of a series of soluble pyridinium-type polymers with different compositions against Escherichia coli (E. coli ) suspended in sterilized distilled water was investigated by a colony count method. The results show that the antibacterial activity of the soluble pyridinium-type polymers is characterized by their activity to kill bacterial cells and this activity can be enhanced as the content of the pyridinium group ( C q ) in the polymers increases. The species of the bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 1 publication
0
66
0
Order By: Relevance
“…Other studies have indicated that the mechanism of antimicrobial activity of ionic liquids is via membrane disruption. This seems likely given the structural similarity between ionic liquids and antimicrobial agents whose mechanism is more fully elucidated (Li et al, 1998;Pernak et al, 2001). Many ionic liquids have a similar structure to cationic surfactants whose primary mode of action membrane-bound protein disruption (Bernot et al, 2005).…”
Section: Antimicrobial and Antibiofilm Activities Of Ionic Liquidsmentioning
confidence: 99%
“…Other studies have indicated that the mechanism of antimicrobial activity of ionic liquids is via membrane disruption. This seems likely given the structural similarity between ionic liquids and antimicrobial agents whose mechanism is more fully elucidated (Li et al, 1998;Pernak et al, 2001). Many ionic liquids have a similar structure to cationic surfactants whose primary mode of action membrane-bound protein disruption (Bernot et al, 2005).…”
Section: Antimicrobial and Antibiofilm Activities Of Ionic Liquidsmentioning
confidence: 99%
“…[5] Polymers containing quaternary nitrogen functionalities have been commonly used as biocidal agents. [6][7][8][9][10][11][12][13][14][15] A number of polymeric disinfectants based on quaternary pyridinium groups, either in the backbone or as pendant groups, have been prepared, which show good activity against bacteria. Recently, Gao and coworkers synthesized random copolymers of acrylamide and vinyl pyridine of varying MWs and pyridine content, which were subsequently quaternized with dimethyl sulfate.…”
Section: Introductionmentioning
confidence: 99%
“…E. coli were incubated at 37°C for 24 h on a nutrient agar plate. Then, the bacterial cell suspensions were prepared as described before, 5 with sterile distilled water used as the suspending medium.…”
Section: Bacteriamentioning
confidence: 99%
“…Along with increasing the filtration rate, it is unfavorable for samples to adsorb or adhere bacterial cells at a shorter contact time; therefore, the extent of removal is lower. Because there is a strong adherence between A 1 2.57 ϫ 10 5 5.05 ϫ 10 4 2.81 ϫ 10 3 4.23 ϫ 10 2 28 A 5 2.02 ϫ 10 4 5.03 ϫ 10 3 6 0 0 a N (inf.) , 5.61 ϫ 10 6 cells/mL; filtration rate, 7.5 mL/min; collected effluent bacterial volume, 20 mL.…”
Section: Effect Of the Viable Bacterial Cell Concentrations In The Inmentioning
confidence: 99%
See 1 more Smart Citation